2018
DOI: 10.1088/1748-3190/aacd5e
|View full text |Cite
|
Sign up to set email alerts
|

Design of a dynamic sonar emitter inspired by hipposiderid bats

Abstract: The ultrasonic emission of the biosonar systems of bats, such as Old World leaf-nosed bats (family Hipposideridae) and the related horseshoe bats (family Rhinolophidae), is characterized by a unique dynamics where baffle shapes ('noseleaves') deform while diffracting the outgoing wave packets. As of now, nothing comparable to this dynamics has been used in any related engineering application (e.g. sonar or radar). Prior work with simple concave baffle shapes has demonstrated the impact of the dynamics on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The independently controlled actuators used in the present design were able to produce eight visibly unique bending profiles providing a level of control over the pinna deformation that is significantly greater than what has been achieved in previous versions of the sonar head [19][20][21]. Additionally, interactions between the simultaneous inflations of different elastomeres were observed that could be the result of changes to the load of one actuator through the action of another.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The independently controlled actuators used in the present design were able to produce eight visibly unique bending profiles providing a level of control over the pinna deformation that is significantly greater than what has been achieved in previous versions of the sonar head [19][20][21]. Additionally, interactions between the simultaneous inflations of different elastomeres were observed that could be the result of changes to the load of one actuator through the action of another.…”
Section: Discussionmentioning
confidence: 82%
“…Here we introduce a biomimetic robotic sensor system for active information encoding, in which we have realized a complete perception-action loop inspired by bats. This design is the latest in a sequence of prototypes we have designed and built to understand the impact of moving noseleaves and/or pinnae [16][17][18][19][20]. Previous prototypes have demonstrated how changing conformation states [21] and fast moving pinnae [15] can create observable changes in the acoustic characteristics of the sensory system.…”
Section: Introductionmentioning
confidence: 99%
“…They can balance sensor range, opening angle, and spatial resolution using techniques such as modulating sound frequency [19], temporal shape of the sound wave signal [20], or sound direction [21]. To create and analyze acoustic signals, they may also actively move their nose leaves and pinnae, which has inspired engineers to build biomimetic emitters and receivers [22][23][24]. With multiple receivers, it is possible to localize a sound source based on the time difference of arrival of the sound to different receivers, as shown in the literature [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Besides relying on the static geometry of their noseleaves, both rhinolophid and hipposiderid bats also have the ability to alter their noseleaf shapes during pulse emission through muscular actuation [6]. Numerical and biomimetic robotic studies have suggested that these dynamic noseleaf deformations can alter the shape of the emission beam and hence, add a time-dependence to the emission characteristics which hence becomes a function of direction, frequency, and time [5,7,8]. Information-theoretic analysis has shown that the time dimension could support the encoding of additional, useful sensory information [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…If the time and frequency dimension are of similar importance to the biosonar sense, we would expect them to be similar in terms of their information coding capacity. Since representing a function of three independent variables requires more data than could be obtained from a behaving animal under controlled conditions, we have used a biomimetic reproduction of a hipposiderid noseleaf ( Figure 1a-c, [7]) to collect the experimental data. Based on this data, we have assessed the information coding capacity using differential entropy because it is a good match for our continuous data and does not require an arbitrary discretization [12].…”
Section: Introductionmentioning
confidence: 99%